2001
DOI: 10.1210/en.142.9.3857
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Evidence for Stimulation of Placental, Myometrial, and Endometrial Prostaglandin G/H Synthase 2 by Fetal Cortisol Replacement after Fetal Adrenalectomy

Abstract: Fetal glucocorticoid-induced premature labor in sheep is an established model of premature labor. However, the pathways by which fetal cortisol triggers subsequent maternal endocrine changes, including enhanced PG synthesis, leading to labor are unclear. The current study was undertaken to determine whether cortisol administration to adrenalectomized fetuses to clamp fetal cortisol at levels present early in the late gestation rise, which are inadequate to produce labor, can stimulate placental, myometrial, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…In the present study, failure of fetal cortisol to rise in the estradiol-treated groups, compared with controls, indicates that the increased PG production by maternal intrauterine tissues is regulated by an estrogen-dependent pathway (4,5). However, other factors, such as oxytocin, recruited by estradiol may play a role in mediating estradiol's effect on induction of PG synthesis.…”
Section: Discussionmentioning
confidence: 45%
See 4 more Smart Citations
“…In the present study, failure of fetal cortisol to rise in the estradiol-treated groups, compared with controls, indicates that the increased PG production by maternal intrauterine tissues is regulated by an estrogen-dependent pathway (4,5). However, other factors, such as oxytocin, recruited by estradiol may play a role in mediating estradiol's effect on induction of PG synthesis.…”
Section: Discussionmentioning
confidence: 45%
“…Although our data support a role for estradiol in the regulation of PG synthesis by intrauterine, nontrophoblast tissues, we cannot exclude the regulatory function of estradiol on trophoblast tissues because administered estradiol was increased only in the maternal plasma. However, in light of the observation that fetal placental PGHS2 increases in late gestation (7), well before the rise in maternal plasma estradiol at the end of gestation, we and others have proposed that in late gestation fetal adrenal cortisol induces fetal placental PGHS2 expression and PG production (4,5). Indeed, we recently reported that fetal cortisol at concentrations seen in late gestation, independent of any other steroids of fetal origin, are able to stimulate fetal placental PGHS2 expression (5).…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations